1988
DOI: 10.1203/00006450-198802000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine as an Indicator of Hypoxia: Its Role in Health and Disease through Free Radical Production

Abstract: Hypoxia is a common insult during the perinatal and neonatal period. New and better ways to evaluate hypoxia are needed. In 1975 we demonstrated high concentrations of the purine metabolite hypoxanthine in umbilical cord plasma after intrauterine hypoxia and proposed that hypoxanthine could be used as an indicator of hypoxia (1). Since then a large number of studies have been published dealing with different aspects of hypoxanthine in hypoxia. However, investigators in this field have encountered several metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
212
0
6

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(223 citation statements)
references
References 84 publications
5
212
0
6
Order By: Relevance
“…The total area of the endothelium in humans is equal to that of 6 tennis courts, with most of the endothelium covering capillary vessels [17]. Capillary XOR plays a major role in redox maintenance of the whole body [16,18] and takes part in various acute pathophysiologies, such as ischemia-reperfusion injury via XDH → XO conversion [9,19,20]. Besides, XDH → XO conversion is essential for the lactation process, a fundamental function of mammals [21].…”
Section: Discussionmentioning
confidence: 99%
“…The total area of the endothelium in humans is equal to that of 6 tennis courts, with most of the endothelium covering capillary vessels [17]. Capillary XOR plays a major role in redox maintenance of the whole body [16,18] and takes part in various acute pathophysiologies, such as ischemia-reperfusion injury via XDH → XO conversion [9,19,20]. Besides, XDH → XO conversion is essential for the lactation process, a fundamental function of mammals [21].…”
Section: Discussionmentioning
confidence: 99%
“…XDH shows a preference for NAD ϩ reduction at the FAD reaction site (although it still displays considerable reactivity with oxygen), whereas XO fails to react with NAD ϩ and exclusively uses dioxygen as its substrate, leading to formation of superoxide anion and hydrogen peroxide (1,7). Previous investigations have suggested that the XDH͞XO conversion is related to milk lipid secretion (8,9) and is implicated in diseases characterized by oxygen radical-induced tissue damage such as postischemic reperfusion injury (10)(11)(12)(13). Thus, the XDH͞XO transition has attracted much attention from both basic and clinical researchers, not only because of the mechanistic interest in the different reactivity of FAD toward NAD ϩ or oxygen substrates (1, 7) but also because of the biological or pathological significance (14).…”
mentioning
confidence: 99%
“…Oxygen-derived free radicals play an important role in experimentally induced hypoxic-reoxygenation injury (4,5), and may be responsible for both hypoxic and hyperoxic aspects of pulmonary damage (6)(7)(8). One source of oxidant genertion in the lungs may be the Hx-XO system (6).…”
mentioning
confidence: 99%